Fish oil supplementation and physical exercise during the development period increase cardiac antioxidant capacity in Wistar rats - Janatar Stella Vasconcelos de Melo; Patrícia Fortes Cavalcanti de Macêdo; Laís Alves Ribeiro Costa; Manuella Batista-; Diorginis José Soares Ferreira (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: To investigate if treadmill exercise (Ex) associated with fish oil (FO) supplementation during lactation would influence the biochemical profile as well as the oxidative balance in the hearts of male juvenile rats. Methods: Fifteen days-old rats were submitted to a daily moderate Ex training (based on their maximal running capacity) and FO supplementation for 4 weeks. Forty-eight hours after the last exercise session, blood fasting glucose and lipid profile were assessed according to the manufacturer's recommendations, while the oxidative status of the hearts was evaluated via colorimetric and absorbance-based assays. Results: FO associated with Ex decreased triglycerides (TG-79.27 ± 5.75 to 60.24 ± 6.25 mg/dL) and very-low-density lipoprotein cholesterol levels (VLDL-15.85 ± 1.15 to 12.05 ± 1.25 mg/dL) when compared to sedentary animals. FO, alone, reduced atherogenic index (AI- 1.14 ± 0.03 vs. 1.01 ± 0.04 a.u) while increased high-density lipoprotein cholesterol (HDL-43.90 ± 2.50 vs. 59.43 ± 3.15 mg/dL) of sedentary animals. Additionally, both Ex (67.3 ± 13.5 nmol/mg prot) and FO supplementation (56.6 ± 5.5 nmol/mg prot) decreased the oxidative damage to lipids in non-trained animals (105.8 ± 10.8 nmol/mg prot). The interventions also protected the protein content from oxidative stress (Ex- 5.15 ± 0.46; FO- 4.5 ± 0.5; and vehicle sedentary-7.3 ± 0.6 µmol/mg prot), while increasing the antioxidant defense and oxidative metabolism. Conclusion: Our findings suggest that intervention in juvenile rats can improve cardiac metabolism. These are the first findings to show the positive effects of the association between FO and moderate treadmill Ex during the critical period of development. We believe these results can drive early-life origins of heart disease through different avenues and, possibly, assist the development of a heart disease prevention program as well as an adjunctive therapeutic resource.